Are there no wage returns to compulsory schooling in Germany? A reassessment. (30th August 2021) - Cygan‐Rehm, Kamila
Summary: This study replicates and challenges the finding of zero wage returns to compulsory schooling in Germany by Pischke and von Wachter ( Review of Economics and Statistics, 90(3), 592–598 ), which is unusual in the literature yet widely cited and until now uncontradicted. I document that this finding is sensitive to minor changes in sample restrictions and model specification. Further results suggest that their estimates are potentially confounded by previously unconsidered institutional details. These findings render the conclusion that compulsory schooling in Germany yields no wage returns at a minimum controversial.